Find the infimum value of
( a − b ) ( a − c ) a 3 + ( b − a ) ( b − c ) b 3 + ( c − a ) ( c − b ) c 3
If a b c = 1 and a , b and c are positive real numbers.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Vicky Vignesh You have not shown when the equality occurs.(Does it?)
Log in to reply
Look at last 8 steps.
In the last step a + b + c ≥ 3 so minimum value of a + b + c = 3
Log in to reply
And when does that happen?
Log in to reply
@Milind Prabhu – It happens when a + b + c = 3 .
Log in to reply
@Viki Zeta – Note that any three positive numbers that sum up to three don't necessarily also have a product of 1. To show that the minimum actually occurs it is necessary to give three numbers which satisfy the conditions that they are required to satisfy.
Log in to reply
@Milind Prabhu – Who said the product is 3 and where? It's clearly given that the product is 1
Log in to reply
@Viki Zeta – Sorry I meant product equal to 1 .
@Milind Prabhu – You must take numbers such that sum is greater than or equal to 3 and product is 1. You must look at conditions given in the question than assuming one such.
Hey you there?
Problem Loading...
Note Loading...
Set Loading...
( a − b ) ( a − c ) a 3 + ( b − a ) ( b − c ) b 3 + ( c − a ) ( c − b ) c 3 = ( a − b ) ( a − c ) a 3 − ( a − b ) ( b − c ) b 3 + ( a − c ) ( b − c ) c 3 = ( a − b ) ( a − c ) ( b − c ) a 3 ( b − c ) − b 3 ( a − c ) + c 3 ( a − b ) = ( a − b ) ( a − c ) ( b − c ) a 3 b − a 3 c − b 3 a + b 3 c + c 3 a − c 3 b = ( a − b ) ( a − c ) ( b − c ) a 3 b − b 3 a − a 3 c + b 3 c + c 3 a − c 3 b ) = ( a − b ) ( a − c ) ( b − c ) a b ( a 2 − b 2 ) − c ( a 3 − b 3 ) + c 3 ( a − b ) = ( a − b ) ( a − c ) ( b − c ) a b ( a + b ) ( a − b ) − c ( a − b ) ( a 2 + a b + b 2 ) + c 3 ( a − b ) = ( a − b ) ( a − b ) ( a − c ) ( b − c ) a b ( a + b ) − c ( a 2 + a b + b 2 ) + c 3 = ( a − c ) ( b − c ) a 2 b + b 2 a − a 2 c − a b c − b 2 c + c 3 = ( a − c ) ( b − c ) a 2 b − a 2 c − b 2 c + c 3 + b 2 a − a b c = ( a − c ) ( b − c ) a 2 ( b − c ) − c ( b 2 − c 2 ) + a b ( b − c ) = ( a − c ) ( b − c ) a 2 ( b − c ) − c ( b + c ) ( b − c ) + a b ( b − c ) = ( a − c ) a 2 − c ( b + c ) + a b = ( a − c ) a 2 − b c − c 2 + a b = ( a − c ) a 2 − c 2 − b c + a b = ( a − c ) ( a + c ) ( a − c ) + b ( a − c ) = a + b + c ∴ ( a − b ) ( a − c ) a 3 + ( b − a ) ( b − c ) b 3 + ( c − a ) ( c − b ) c 3 = a + b + c Using AM-GM inequality, and noting a, b, c are distinct 3 a + b + c > 3 a b c a b c = 1 ⟹ 3 a + b + c > 1 ⟹ a + b + c > 3 ∴ ( a − b ) ( a − c ) a 3 + ( b − a ) ( b − c ) b 3 + ( c − a ) ( c − b ) c 3 = a + b + c > 3